Pengaruh Model Pembelajaran Discovery Learning Terhadap Minat Belajar Siswa dalam Mata Pelajaran Pendidikan Agama Kristen dan Budi Pekerti Kelas VIII SMP Negeri 1 Sianjur Mulamula Kecamatan Sianjur Mulamula Kabupaten Samosir Tahun Pembelajaran 2023/2024 - Rame Febrianti Simanullang; Binur Panjaitan; Oktober Tua Aritonang; Lince Sihombing; Wilson Simanjuntak (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
The purpose of this research is to find out whether there is an influence of the Discovery Learning Learning Model on Interest in Learning Christian Religious Education and Characteristics of Class VIII Students of SMP Negeri 1 Sianjur Mulamula, Sianjur Mulamula District, Samosir Regency, Academic Year 2023/2024. The method used in this research is a quantitative method with a pre-experimental research type with a "One Group Pretest-Posttest Design" design. The population is all students in class VIII of SMP Negeri 1 Sianjur Mulamula, Sianjur Mulamula District, Samosir Regency for the 2023/2024 academic year who are Protestant Christians, totaling 140 people and a sample of 32 people was determined using purposive sampling. Data was collected using a closed questionnaire with 20 items. The results of data analysis show that there is a significant influence of the discovery learning learning model on students' interest in learning in the subject of Christian Religious Education and Character Education for Class VIII Students of SMP Negeri 1 Sianjur Mulamula, Sianjur Mulamula District, Samosir Regency, Academic Year 2023/2024, proven by the significant test obtained by the value tcount > ttable (α=0.05; dk=n-1=31) which is 7.809 > 2.042, thus there is a significant influence between variable X and variable Y. Thus H0 is rejected and Ha is accepted.